2018
DOI: 10.1038/s41556-018-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β inflammatory response driven by primary breast cancer prevents metastasis-initiating cell colonization

Abstract: Lack of insight into mechanisms governing breast cancer metastasis has precluded the development of curative therapies. Metastasis-initiating cancer cells (MICs) are uniquely equipped to establish metastases, causing recurrence and therapeutic resistance. Using various metastasis models, we discovered that certain primary tumours elicit a systemic inflammatory response involving interleukin-1β (IL-1β)-expressing innate immune cells that infiltrate distant MIC microenvironments. At the metastatic site, IL-1β ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 71 publications
5
89
0
Order By: Relevance
“…B cells played the imperative role in the TME from various tumor samples, particularly in the ccRCC, with a mean of 4% across samples 4 cells had been established as a metastasis-promoter in bladder cancer 9 while opposite effects were also reported showing B cells could suppress other types of tumor development 32 . In the present study, we used in vitro migration assays, invasion assays, 3D invasion assays and in vivo tail vein injected mouse model to show that TEB cells could promote RCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells played the imperative role in the TME from various tumor samples, particularly in the ccRCC, with a mean of 4% across samples 4 cells had been established as a metastasis-promoter in bladder cancer 9 while opposite effects were also reported showing B cells could suppress other types of tumor development 32 . In the present study, we used in vitro migration assays, invasion assays, 3D invasion assays and in vivo tail vein injected mouse model to show that TEB cells could promote RCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences showed that IL-1β level was increased in a variety of human tumors 35 . Specifically, Sandra McAllister reported that IL-1β inflammatory response driven by primary breast cancer prevents metastasis-initiating cell colonization 32 . Regulatory B cells (Bregs), an important B cell subset producing IL-10, had been shown to contribute to autoimmune diseases, cancers, and chronic infections, which provided a possible mechanism how B cells turned into a tumor-promoter 36 .…”
Section: Discussionmentioning
confidence: 99%
“…At primary sites, IL-1 has been shown to promote tumor growth 7,29 . However, at secondary sites, studies suggest both prometastatic and antimetastatic roles for IL-1 signaling in models of breast cancer 30,31 . The divergent IL-1 responses in metastasis may be explained by different breast cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…34 IL-1 signaling has also been associated with increased chemoresistance in mouse models of cancer 35 and production of protumorigenic IL-22. 36 In prognostic studies, higher tumor IL-1β levels have been associated with improved survival of patients with lymph node-positive breast cancer, 37 while the use of a blocking anti-IL-1β antibody in patients with cardiovascular diseases showed a reduction on lung cancer incidence. 38 Extracellular ATP activates NLRP3 inflammasome through P2×7 receptors.…”
Section: Introductionmentioning
confidence: 99%